PENGARUH HARGA, PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI PEACOCKOFFIE, SEMARANG - Anggun Setya Ningrum; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2019)
The rapid growth of coffee shops in a few years has made competition even tighter. Consumer behavior in decision making is influenced by several factors including price, product, and location. Peacockoffie is one of the well-known coffee shops in the city of Semarang. The problem in this research is what caused the increase and decrease in Peacockoffie's annual sales turnover in the period 2013 to 2017 amid the mushrooming of coffee shops in Semarang City. The results of the study show that the price, product, and location variables have a positive and significant influence on purchasing decisions. Of the three variables analyzed, product variable coefficients are greater than price variables and location variables. From the three variables also obtained results that the price variable has a greater influence on the purchasing decisions of Peacockoffie Semarang, which is equal to 0.955, while the location variable is 0.776 and the product variable is 0.687. The results of this study indicate that although price variables are relatively cheap, product variables are considered satisfactory, and location variables are quite strategic, but there are other factors that influence consumer purchasing decisions in Peacockoffie Semarang, ie consumers do not make Peacockoffie a top priority compared to other existing coffee shops in the city of Semarang. The researcher suggested that Peacockoffie improve the quality of the products offered, such as adding more innovations in the products offered and in the presentation of products to be a product advantage compared to other coffee shops. As well as enhancing branding, Peacockoffie is a comfortable and good place to enjoy coffee.